Comparison of different locking mechanisms in total hip arthroplasty: relative motion between cup and inlay - Jäger, Sebastian; Uhler, Maximilian; Schröder, Stefan; Beckmann, Nicholas A.; Braun, Steffen (Materials, 2020)
The resulting inflammatory reaction to polyethylene (PE) wear debris, which may result in osteolysis, is still considered to be a main reason for aseptic loosening. In addition to the primary wear in hip joint replacements caused by head-insert articulation, relative motions between the PE liner and the metal cup may cause additional wear. In order to limit this motion, various locking mechanisms were used. We investigated three different locking mechanisms (Aesculap, DePuy, and Zimmer Biomet) to address the resulting relative motion between the acetabular cup and PE liner and the maximum disassembly force. A standardized setting with increasing load levels was used in combination with optically based three-dimensional measurements. In addition the maximum disassembly forces were evaluated according to the ASTM F1820-13 standard. Our data showed significant differences between the groups, with a maximum relative motion at the maximum load level (3.5 kN) of 86.5 ± 32.7 µm. The maximum axial disassembly force was 473.8 ± 94.6 N. The in vitro study showed that various locking mechanisms may influence cup-inlay stability.
Gesehen am 02.06.2020